Analysis of the Influence of Product Quality and Price on Consumer Repurchase Decisions for Pemuda Brand Bread in Ambon City Mediated by Consumer Satisfaction - Siahainenia, Silfiena; Tamher, Etvin R; Laitupa, Abdul Azis (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the influence of product quality and price on repurchase decisions with consumer satisfaction as a mediating variable. Using a quantitative explanatory approach, data were collected through questionnaires from 200 active consumers of Pemuda brand bread, and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that product quality does not directly influence repurchase decisions, but has a significant effect on consumer satisfaction. Conversely, price has a direct and significant effect on repurchase decisions, although it does not influence consumer satisfaction. Consumer satisfaction proved to be a strong mediator, where price influences repurchase decisions indirectly through consumer satisfaction, while the indirect effect of product quality through satisfaction was not significant. The research model showed a Goodness of Fit (GoF) of 0.689, which is categorized as a large effect. These findings reveal the unique dynamics of consumers in Ambon city where they are more responsive to perceived value and price fairness than technical attributes of quality alone. Theoretically, this study extends the validity of Expectation Confirmation Theory to the context of food MSMEs in Maluku and practically, the results provide strategic guidance for local business actors to strengthen loyalty through quality consistency, proportional pricing strategies, and holistic consumer experience management.